ANALISIS KEPUASAN NASABAH DAERAH PINGGIRAN TERHADAP KUALITAS PELAYANAN DI BANK ACEH CABANG PEMBANTU SUBULUSSALAM - Mikhral Rinaldi; Sajim, Sajim (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2023)
This study aims to analyze customer satisfaction from the outlying areas towards the services provided by the Bank Aceh Subulussalam Branch Office. The main focus of the study is to understand how service aspects such as responsiveness, reliability, empathy, assurance, and physical evidence affect customer satisfaction from remote areas. The research method used is a qualitative approach with a qualitative descriptive method, collecting data through interviews and direct observation of 15 customers from outlying areas. The results of the study indicate that customers from outlying areas are satisfied with the services provided by the bank. This satisfaction is influenced by several factors, including the quality of the bank's physical facilities, the reliability and responsiveness of employees, and the attention and assurance provided. Fair service without distinguishing the customer's area of ​​origin, friendly and professional attitudes from employees, and concern for the specific needs of customers such as assistance in filling out forms and providing health facilities during the COVID-19 pandemic, are key factors in increasing customer satisfaction. This study concludes that Bank Aceh Subulussalam Branch Office has succeeded in providing good and satisfactory service to customers from various backgrounds, including those from outlying areas. Therefore, it is recommended that banks continue to maintain and improve the quality of service to maintain customer satisfaction and increase their loyalty. Customers are expected to actively ask and communicate with the bank if they need help so that the transaction process runs smoothly and effectively